The population genetic consequences of habitat fragmentation for plants - Young, A.G.; Boyle, T.J.B.; Brown, A.H.D. (1996)
Habitat fragmentation reduces the size and increases the spatial isolation of plant populations. Initial predictions have been that such changes will be accompanied by an erosion of genetic variation and increased interpopulation genetic divergence due to increased random genetic drift, elevated inbreeding and reduced gene flow. Results of recent empirical studies suggest that while genetic variation may decrease with reduced remnant population size, not all fragmentation events lead to genetic losses and different types of genetic variation (e.g. allozyme and quantitative variation) may respond differently. In some circumstances, fragmentation actually appears to increase gene flow among remnant populations, breaking down local genetic structure.